Diagenetic Mg-rich calcite in Mediterranean sediments: quantification and impact on foraminiferal Mg/Ca thermometry - Boussetta S.; Bassinot F.; Caillon N.; Nouet J.; Kallel N.; Rebaubier H.; Klinkhammer G.; Labeyrie L.; SABBATINI, ANNA (Marine Geology, 2011)
Mg/Ca ratios in planktonic foraminifera have been developed into a powerful tool in paleoceanography to reconstruct past sea surface temperatures (SST). However, additional factors that might have an influence on Mg/Ca, like dissolution, salinity, diagenesis, and carbonate ion effects have come into focus. In this paper, the occurrence of diagenetic calcification and its potential effects on Mg/Ca have been studied using 20 wellpreserved core tops recovered from the Mediterranean Sea. Analyses were performed on two planktonic foraminifer species; Globigerinoides ruber and Globigerina bulloides using ICP-AES Mg/Ca measurements, SEM observations and X-ray diffractometry analyses. Foraminiferal Mg/Ca values are higher than those obtained in the open sea. The highest values were found in the Eastern Mediterranean basin. These anomalies cannot be simply explained by a salinity effect because Mg/ Ca ratios, when corrected for temperature influence, do not display any significant correlation with salinity. Our results seem to indicate that diagenesis can account for anomalously high Mg/Ca values. Indeed, SEM observations show aggregates of rhombohedral crystals that could be interpreted as secondary calcite overgrowths. We note also the occurrence of numerous coccoliths trapped in foraminifer walls and covered with a secondary mineral phase. X-ray diffraction diagrams of numerous foraminiferal samples exhibit peak of Mg-rich calcite (10–12%) associated with the usual foraminifer calcite peak. It has been demonstrated that this calcite highly rich in Mg, is compatible with an inorganic calcite precipitated directly from seawater. The deconvolution of the main XRD peak (104) shows that the percentage of Mg-rich calcite can reach up to ~21% of the total foraminiferal calcite in the Eastern basin whereas in the western Mediterranean Sea, proportions do not exceed 5%. In addition, we demonstrate that, the diagenetic process is very heterogeneous (even at the sample scale) and is not simply a reflection of ΔCO3 at the sea ...